The art of the Japanese garden : history, culture, design - Young, David E. (Tuttle Publishing, 2019)
Japanese gardens are rooted in two traditions: an ancient one in which patches of gravelled forest or pebbled beach were dedicated to nature spirits, and a tradition from China and Korea that included elements such as ponds, streams, waterfalls, rock compositions, and a variety of vegetation. This book traces the development and blending of these two traditions, while also providing insight into modern Japanese gardening trends. The Art of the Japanese Garden is a comprehensive collection of the most notable gardens in Japan including gravelled courtyards, early aristocratic villas, palace gardens, esoteric and paradise gardens, Zen gardens, warrior gardens, tea gardens, and stroll gardens. With an impressive amount of new content, including more than 30 images, this updated edition offers inspiring ideas for your own trip to Japan. If you're just dreaming of traveling to Japan, there is also a section on Japanese gardens in other countries get a taste of Japanese culture and tradition closer to home. Japanese gardening has reached new heights of sophistication, and serves as garden design and landscaping inspiration all over the world. The Art of the Japanese Garden introduces readers to the history, culture, and design behind these large-scale works of art.